4-Chloro-2-methyl-N-(2-methylphenyl)benzenesulfonamide - B. Thimme Gowda; Sabine Foro; P. G. Nirmala; Hiromitsu Terao; Hartmut Fuess (Acta Crystallographica Section E, 2009)
In the crystal structure of the title compound, C14H14ClNO2S, the two aromatic rings are tilted relative to each other by 45.8 (1)°. In the crystal, inversion dimers linked by pairs of N—H...O hydrogen bonds occur.